Critical analysis on the use of Epi-No in pregnancy and delivery - Mendes, Nathalia Antal; Mazzaia, Maria Cristina; Zanetti, Miriam Raquel Diniz (ABCS Health Sciences, 2018)
Currently methods are reported that favor the stretching and prevent pelvic floor injuries in vaginal delivery, such as perineal massage and the Epi-No balloon. This device is well accepted by patients but results for prevention of episiotomy and perineal lesions at birth are controversial. The aim of this study was to evaluate the purpose, method, frequency, teaching/guidance of the use of the Epi-No during pregnancy and childbirth. A narrative review was prepared with a survey of available literature about the use of the Epi-No during pregnancy and childbirth in PUBMED, BVS and SciELO databases in Portuguese and English. 837 articles were found, only 9 articles met the inclusion criteria established. Information from papers were summarized in tables covering the relevant aspects. Factors such as the time, period, positioning and the process of teaching/guidance should be better described and standardized, so it would be possible to investigate the effectiveness of its use in the outcomes in the perineal vaginal delivery.